Cholecystectomy for Complicated Gallbladder and Common Biliary Duct Stones: Current Surgical Management - Argiriov, Yanna; Dani, Melanie; Tsironis, Christos; Koizia, Louis J. (Frontiers in Surgery, 2020)
Gallstone disease accounts for the vast majority of acute surgical admissions in the UK, with a major treatment being cholecystectomy. Practice varies significantly as to whether surgery is performed during the acute symptomatic phase, or after a period of recovery. Differences in practice relate to operative factors, patient factors, surgeon factors and hospital and trust wide policies. In this review we summarize recent evidence on management of gallstone disease, particularly with respect to whether cholecystectomy should occur during index presentation or following recovery. We highlight morbidity and mortality studies, cost, and patient reported outcomes. We speculate on barriers to change in service delivery. Finally, we propose potential solutions to optimize care.